Comparative legal method of research: a new role in the conditions of globalization - V. V. Kopcha; V. V. Lemak (Bulletin of Kharkiv National University of Internal Affairs, 2018)
Particular attention is paid to the issue of the growth of the role of the comparative legal method, the method of its conduct, as well as the factors that determine the growth of its role. First, it is noted that after the World War II the universally recognized principles of international law have been developed and consolidated in the UN Charter and in other fundamental international legal instruments. Speaking as a product of customary international law (that is the result of the practice of civilized nations in relations between themselves and with societies), they have become universal in character, which puts them “at the apex” of world order. Such principles as respect for human rights, state sovereignty, and territorial integrity of states have received generally accepted content. In many European countries they have “immediate effect”, gaining constitutional character. This means that within the framework of national legal systems a new phenomenon has been created, which is really a common archetype present in the constitutional system of every civilized state. Secondly, comparative law is used today as an instrument for judicial investigation of a legal case and, therefore, the argumentation of a court decision. This approach is widespread in the practice of higher courts of states and in particular the European Court of Human Rights.Conclusions have been made that after the World War II there was no significant legislative project, which to one degree or another would not be accompanied by extensive comparative legal research. Such an approach should be reflected in the practice of reform in Ukraine. It is important to emphasize that the comparative approach is inherent not only for science, but also for law-making and law-enforcement bodies (courts). An adequate methodology of a comparative legal approach takes into account a comprehensive understanding of the law itself (written and unwritten), as well as its broad social context.In addition, the change in the nature of international law, the development in the past three decades of full-fledged regional law-enforcement (for example, European rule of law), as well as the strengthening of their interplay with national legal orders, necessitates the use of so-called “vertical methods” of comparative research.